CHILD SEXUAL HARASSMENT LAW ENFORCEMENT POLICY - Vorawee, Jugkrit; Khongwan, Sonthon (Rangsit Journal of Law and Society, 2022)
Violence against children considers as a violation of human rights as in the Convention on the Rights of the Child. It defines that every child has the right to survive, grow, and be protected from all forms of violence. Every child has the right to respect human dignity, physical and psychological integrity, and equal protection. Child Sexual Harassment is violence committed against children which causes severe physical and mental consequences. It damages committed children in the present and future which considers as a challenging problem in every country and every society. Law enforcement of child sexual harassment must be true protection for child benefit. This academic article aims to study the condition of problems and flaws of the criminal justice system regarding child sexual harassment. The study has found that problems such as complaints, physical evidence, expert standard, inequality between sexually harassed and sexually accused affect the law enforcement and practice in the prosecution of child sexual harassment cases. So, harassed children are not truly protected for their benefit. It is proposed to have a process such as a medical protection process when a child is being sexually harassed, a social protection process, assistance, and remedy process including the amendment of criminal code for sexual harassment, which conforms to the appropriate forms of offending that changing in today’s society. Thus, the criminal justice system on child sexual harassment can protect the rights of harassed children more effectively.